The Impact of COVID-19 Pandemic on the Performance of Indonesian MSME with Innovation as Mediation - Agung Sudjatmoko; Mohammad Ichsan; Marcella Astriani; Mariani; Angeline Clairine (Cogent Business & Management, 2023)
This paper investigates how the impact of the COVID-19 pandemic crisis affects the innovation of Micro, small and medium enterprises (MSME) in Indonesia and how innovation, namely product, process, marketing, and organizational innovation, acts as a mediator for MSME performance. An integrated conceptual framework is developed and empirically tested using cross-sectional survey design data from 300 MSME owners in Indonesia. Structural Equation Modelling (SEM) software Smart PLS examines the hypotheses testing. Descriptive analysis is also used to provide demographic data of the owners of MSMEs in Indonesia. This study reveals that the COVID-19 pandemic crisis significantly and positively impacts four dimensions of innovation. The results indicate that the pandemic triggered the MSME owners to innovate or adapt. This study also found that four dimensions of innovation partially mediate the COVID-19 pandemic crisis and MSME performance relationship. The results show that product, marketing, and organizational innovation significantly impact MSME performance. With marketing innovation as the lowest innovation dimension that affects performance, and organizational innovation as a major contributor that significantly impacts MSME performance. However, the results also demonstrate that among the four dimensions of innovation, process innovation does not significantly impact MSME performance which is highlighted by an indicator such as reducing production cost. This shows that reducing production costs is optional and does not mean that the performance of MSME will increase significantly. Therefore, the findings of this study are set to advance theories in MSME innovation and performance. It also presents important implications for the MSME owners to develop a successful and sustainable MSME industry.
Keywords: 650; COVID-19 pandemic crisis; Indonesian MSME; innovation; marketing innovation; MSME performance; organizational innovation; process innovation; product innovation